Fatores antecedentes e atenuantes de burnout durante a pandemia de COVID-19 - Sant'Ana, Lívia Sousa (2023)
The Covid-19 pandemic has brought significant impacts on the mental health of the global population, including a concerning increase in anxiety and depression levels worldwide. In such context, the study of the burnout syndrome becomes relevant, as the adverse conditions of the pandemic may have exacerbated its incidence. Although the literature on burnout has existed for more than 50 years, it generally focuses on normal work contexts rather than on environments of perceived vulnerability, as seen in the Covid-19 pandemic. Studies in extreme scenarios almost exclusively focus on the directly affected population, such as healthcare professionals. A gap in the literature appears to be the effects of extreme scenarios on indirectly affected workforces. This study aims to contribute to reducing this gap by (a) testing how factors related to work, family, and the pandemic itself are interconnected and can influence burnout syndrome; and (b) analyzing burnout, its anteceding and mitigating factors, based on data from a workforce indirectly affected by the Covid-19 pandemic. Drawing upon the DemandControl-Support (DCS) Model, the study utilized secondary quantitative data originally collected in multiple time points during the pandemic by a financial institution based in São Paulo, Brazil. The results of this study support the multiplication hypothesis, showing that under conditions of perceived vulnerability, the total stress exceeds the mere sum of all anteceding ou atenuating factors, as factors in fact interact with each other in the stress accumulation process and in the development of the burnout syndrom, indicating that the characteristics of the work environment do not act in isolation in the development of chronic occupational stress and the intensification of the mismatch between individual expectations and the presented reality. Our data indicates that the effects of heightened stressors extend beyond frontline sectors and not only enhance our understanding of the relationship between work, family, and mental health in times of crisis but also provide practical insights for people management in organizations facing similar challenges.